Evaluasi Kinerja Operasional Bus Trans Banyumas pada Koridor 1 Pasar Pon – Terminal Ajibarang - dwi nanda; Juanita Juanita (Techno (Jurnal Fakultas Teknik, Universitas Muhammadiyah Purwokerto), 2023)
The Trans Banyumas Bus is a mode of mass transportation owned by the Banyumas Regency Transportation Agency which is managed by PT. Banyumas Raya Transportation with the Buy The Service (BTS) system.. It is hoped that this mode of transportation can reduce the use of private vehicles so as to reduce the level of traffic density. The purpose of this study was to determine the level of operational performance of Trans Banyumas corridor 1 buses in terms of load factor, headway, circulation time, travel speed, downtime and availability of transport and then compared with the minimum service standards contained in the Decree of the Director General of Land Transportation Number 687 year 2002, Regulation of the Minister of Transportation of the Republic of Indonesia No. 10. Year 2012, and Regulation of the Minister of Transportation of the Republic of Indonesia No. 98. Year 2013. This research was conducted using dynamic survey methods and static surveys which were carried out on Sunday, 17 July 2022 and Wednesday, 20 July 2022 starting at 05.00 am until 09.00 pm. From the research results on the two survey days, the operational performance results for each indicator reviewed and which met the minimum service standards were circulation time, travel speed, downtime and transportation availability. Meanwhile, the operational performance indicators that have not met the minimum service standards are load factor and headway. So of the six indicators reviewed, two of them have not met the minimum service standards based on the Decree of the Director General of Land Transportation No. 687 of 2002, Regulation of the Minister of Transportation of the Republic of Indonesia No. 10. Year 2012, and Regulation of the Minister of Transportation of the Republic of Indonesia No. 98. Year 2013.